Shapes of Differential Pulse Voltammograms and Level of Metallothionein at Different Animal Species - Adam, Vojtech; Beklova, Miroslava; Pikula, Jiri; Hubalek, Jaromir; Trnkova, Libuse; Kizek, Rene (Sensors (Basel, Switzerland), 2007)
Metallothioneins play a key role in maintaining homeostasis of essential metalsand in protecting of cells against metal toxicity as well as oxidative damaging. Exceptinghumans, blood levels of metallothionein have not yet been reported from any animalspecies. Blood plasma samples of 9 animal species were analysed by the adsorptive transferstripping technique to obtain species specific voltammograms. Quite distinct records wereobtained from the Takin (Budorcas taxicolor), while other interesting records were observedin samples from the European Bison (Bison bonasus bonasus) and the Red-eared Slider(Trachemys scripta elegans). To quantify metallothionein the catalytic peak Cat2 was used,well developed in the Domestic Fowl (Gallus gallus f. domestica) and showing a very lowsignal in the Red Deer (Cervus elaphus). The highest levels of metallothionein reachingover 20 μM were found in the Domestic Fowl. High levels of MT were also found in theBearded Dragon (Pogona vitticeps) and the Grey Wolf (Canis lupus lupus). The lowestvalues of about 1-3 μM were determined in the Red-eared Slider, Takin and Red Deer. Employing a simple electrochemical detection it was possible to examine variation in blood metallothionein in different species of vertebrates.
Keywords: Bactrian Camel; Domestic Fowl; Red-eared Slider; Reindeer; Brdicka reaction; Bearded Dragon; Catalytic signal; Takin; Electrochemical detection; Red Deer; Heavy metals; Grey Wolf; European Bison